PERAN STAKEHOLDER DALAM PERCEPATAN PENURUNAN STUNTING DI KELURAHAN TANJUNG MAS KOTA SEMARANG - Lusiana Wardhani; Maesaroh Maesaroh; Nina Widowati (Journal of Public Policy and Management Review, 2023)
Stunting is a nutritional problem that is a priority health problem that must be addressed immediately at this time. Reducing stunting rates needs to be done early so that the impact does not continue in the long term, so handling it requires collaboration between stakeholders. In Kelurahan Tanjung Mas, although the program has been implemented, the stunting rate still shows an increase. So, it is still a question of how the role played by stakeholders in the acceleration program to reduce stunting in Tanjung Mas Village. The purpose of this study is to identify and analyze the role of stakeholders in the accelerated stunting reduction program in Tanjung Mas Village, Semarang City and to analyze the supporting or inhibiting factors. This research uses qualitative research methods with data collection techniques through observation, interviews, documentation, and literature study. The theory used in this research is the theory of stakeholder roles by Nugoroho. The results showed that the stakeholders in the stunting reduction acceleration program in Tanjung Mas Village, Semarang City are the Health Office, Puskesmas, Kelurahan, Posyandu, Community and Private. These stakeholders carry out roles that are divided into five, namely policy creator, implementor, coordinator, facilitator, and accelerator. The supporting factors of the stunting reduction acceleration program in Tanjung Mas Village are values and communication. The inhibiting factors in accelerating stunting reduction in Tanjung Mas Village are ineffective communication and limited policy resources. The recommendations given are to increase communication between stakeholders and involve relevant stakeholders in the policy formulation process.